Simulation of the Optimized Structure of a Laterally Coupled Distributed Feedback (LC-DFB) Semiconductor Laser Above Threshold - Seifouri, M.; Faraji, A. (Engineering, Technology & Applied Science Research, 2013)
In this paper, the laterally coupled distributed feedback semiconductor laser is studied. In the simulations performed, variations of structural parameters such as the grating amplitude a, the ridge width W, the thickness of the active region d, and other structural properties are considered. It is concluded that for certain values ​​of structural parameters, the laser maintains the highest output power, the lowest distortion Bragg frequency δL and the smallest changes in the wavelength λ. Above threshold, output power more than 40mW and SMSR values greater than 50 dB were achieved.